واقع الأنثربولوجيافي الجامعةالجزائريةبعد أكثرمن ربع قرن من الإعتراف الأكاديمي - بن قيلة, سلمان (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
This paperaims to monitor the reality of Anthropologyat the Algerian Universitiesduring the currentperiod, as a self-containedknowledge-based or as a module taught in otherknowledgespecialities. The researcherconducts for that a total surfing of all the Algerian universities’ websites as he examines the teaching programs of theirvariouscolleges, and researchlaboratories .He alsocounts the differentuniversities and collegesthatteachAnthropologyor the modules and the specialitiestheyassociatedwith . The researcherreachedthroughthisthatanthropologyisgenerallytaught in the faculties of social sciences and humanities, and the faculties of literature and languages  in differentspecialities and in variousuniversities. He establishes a list of laboratories of scientificresearchthat are active in Algerian universities and specialized in thisfield of knowledge.